THE ROLE OF SOCIAL MEDIA INFLUENCER ON BRAND SWITCHING OF MILLENNIAL AND GEN Z: A STUDY OF FOOD-BEVERAGE PRODUCTS - Hanifawati, Tri; Dewanti, Vivayani Wahyu; Saputri, Ghita Dwi (Jurnal Aplikasi Manajemen, 2019)
Social media is the most popular marketing tools for generation millennial and Z. They are known as the most easily switch brand generation. This research contributes to social media marketing analytic research with an exploration of the role of social media influencer on consumer brand switching decision. Data collected through an online survey used a random sampling technique to 390 Indonesian respondents, 195 data fulfilled the criterion. Data analyzed using Least Square, Mann Whitney, and Paired Sample T-Test method. The results show that opinion leaders, celebrities, and social leaders have a significant and positive effect on brand switching and no different impact on millennials and Gen Z. Referring to switching motivation found that social media has more influence as an opinion leader than celebrities or social leaders. The findings of the study suggested some strategies for managers and influencers on how to manage social media brand promotion based on our findings.